Fast simulations of multidimensional NMR spectra of proteins and peptides. (3rd October 2017) - Vosegaard, Thomas
Abstract : To simulate full multidimensional nuclear magnetic resonance spectra of peptides and proteins in a reasonable time frame, a strategy for separating the time‐consuming full‐density matrix calculations from the chemical shift prediction and calculation of coupling patterns is presented. The simulation setup uses SIMulation Program for SOlid‐state NMR (SIMPSON) to calculate total correlation spectroscopy transfer amplitudes and average distances as a source for nuclear Overhauser effect spectroscopy transfer amplitudes. Simulated 1 H 1D, 2D total correlation spectroscopy, and 2D nuclear Overhauser effect spectroscopy nuclear magnetic resonance spectra of peptides with sequence Pro─Ala─Gly─Tyr─Asn and Asn─Phe─Gly─Ala─Ile─Leu and of ubiquitin are presented. In all cases, the simulations lasted from a few seconds to tens of seconds on a normal laptop computer. Abstract : This paper describes how to achieve instant simulations of multidimensional NMR spectra of peptides and proteins.